2006
DOI: 10.1159/000093702
|View full text |Cite
|
Sign up to set email alerts
|

Male Dominance Rank, Mating and Reproductive Success in Captive Bonobos (Pan paniscus)

Abstract: In the recent past, application of DNA genotyping techniques has enabled researchers to more accurately test relationships between dominance rank (DR), mating success (MS) and reproductive success (RS). Paternity studies often reveal that reproductive outcome does not always correlate with male DR and/or MS and thus open room for discussion and interpretation of alternative reproductive tactics of both sexes. In this study, we analysed male DR, MS and RS in a group of bonobos at Twycross Zoo (UK). Genetic rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Regarding Vehrencamp's (1983) criterion of resource allocation, Vervaecke et al (1999) showed that highranking bonobos in Planckendael had easier access to food. We also found that copulations among male bonobos are not distributed equally (Stevens, unpublished results), which corresponds with findings from wild studies that dominant males obtain more copulations (Kano 1996;Takahata et al 1996), though there is not always a relationship between dominance and mating success (; Furuichi and Hashimoto 2004;Marvan et al 2006).…”
Section: Dominance Hierarchiessupporting
confidence: 88%
“…Regarding Vehrencamp's (1983) criterion of resource allocation, Vervaecke et al (1999) showed that highranking bonobos in Planckendael had easier access to food. We also found that copulations among male bonobos are not distributed equally (Stevens, unpublished results), which corresponds with findings from wild studies that dominant males obtain more copulations (Kano 1996;Takahata et al 1996), though there is not always a relationship between dominance and mating success (; Furuichi and Hashimoto 2004;Marvan et al 2006).…”
Section: Dominance Hierarchiessupporting
confidence: 88%
“…Under such conditions the opportunistic mating strategy in chimpanzee communities offers an opportunity for sperm competition in this species [32] [34] . In contrast, the high social status of females in bonobo communities is unique to this species of Pan [35] , [36] which, coupled to concealed ovulation, could allow greater female choice [37] , and this may act as an evolutionary counterstrategy that diminishes sexual selection via sperm competition. This view is further supported by the observation that relative to chimpanzees, adult bonobos show reduced sex dimorphism in both body size [38] and the canine teeth [39] , [40] .…”
Section: Resultsmentioning
confidence: 99%
“…Low rank of males prohibits them to drive away other males and to force females to mate against their will [53] , [60] . From an evolutionary perspective, competition among males for females may lead to fewer males in the group [64] , [65] , and bigger males, thus to increased sexual dimorphism [66] , and therefore, in extreme cases to stronger male dominance. However, the present study addresses only immediate effects, in which, in contrast, increased aggression with males augments female dominance over males via the winner-loser effect.…”
Section: Discussionmentioning
confidence: 99%